2019
DOI: 10.7150/thno.32260
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cell-Treated Regulatory CD23+CD43+ B Cells Alleviate Intestinal Inflammation

Abstract: Rationale: Mesenchymal stem cells (MSCs) have been demonstrated to ameliorate inflammatory bowel disease by their actions on multiple immune cells, especially on regulatory B cells (Breg cells). However, the phenotypes and functions of human MSCs (hMSCs)-treated Breg cell subsets are not yet clear. Methods: Purified B cells were cocultured with MSCs and the phenotypes and immunomodulatory functions of the B cells were analyzed by FACS and proliferation assays in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 57 publications
0
45
0
2
Order By: Relevance
“…Chen et al found that MSCs can induce a new regulatory B-cell (Breg) population characterized by CD23 + CD43 + phenotypes. These CD23 + CD43 + Breg cells significantly inhibit the secretion of proinflammatory cytokines and the proliferation of T cells through the IL-10–dependent pathway (Carreras-Planella et al, 2019a ; Chen et al, 2019 ). Rafei et al found that MSCs inhibit the expression of transcription factor signal transducer and activator of transcription 3 (STAT3) via chemokine C-C motif chemokine ligand 2 (CCL2) and then induce paired box 5 (PAX5) protein synthesis to inhibit the secretion of immune globulin in plasma cells (Rafei et al, 2008 ) ( Figure 2 ).…”
Section: Roles Of Mscs In Immunomodulationmentioning
confidence: 99%
“…Chen et al found that MSCs can induce a new regulatory B-cell (Breg) population characterized by CD23 + CD43 + phenotypes. These CD23 + CD43 + Breg cells significantly inhibit the secretion of proinflammatory cytokines and the proliferation of T cells through the IL-10–dependent pathway (Carreras-Planella et al, 2019a ; Chen et al, 2019 ). Rafei et al found that MSCs inhibit the expression of transcription factor signal transducer and activator of transcription 3 (STAT3) via chemokine C-C motif chemokine ligand 2 (CCL2) and then induce paired box 5 (PAX5) protein synthesis to inhibit the secretion of immune globulin in plasma cells (Rafei et al, 2008 ) ( Figure 2 ).…”
Section: Roles Of Mscs In Immunomodulationmentioning
confidence: 99%
“…R Chen et al shown that PGE2 could induce B10 cells via the MAPKs/AKT-AP1 axis or aryl hydrocarbon receptor (AhR) signaling (108). Recently, COX-2/PGE2 pathway is also found to involved in MSCs induce CD23 + CD43 + Bregs, which significantly reducing the clinical and histopathological severity of induced colon inflammation and ameliorating gastrointestinal mucosal tissue damage in mice (59). However, IFN-γ-primed MSCs were reported to inhibit the production of IL-10 by LPS-activated B cells through the COX-2 pathway (83).…”
Section: Soluble Molecule Interactionsmentioning
confidence: 99%
“…For instance, M. Franquesa et al experimentally demonstrated that hASCs can act independently of T cells and directly on B cells to promote the production of CD19 + CD24 high CD38 high and IL-10-production regulatory B cells ( 84 ). Although cell-to-cell contact manner have been confirmed to be involved in MSCs inducing Bregs by the transwell co-culture ( 59 , 80 ), little is known about the particular molecules. One of the major molecules involved in this cell-to-cell interaction of MSCs is the costimulatory molecules is programmed death ligand-1 (PD-L1, also known as B7-H1).…”
Section: How Msc S Regulate Breg Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn's disease (CD), are chronic relapsing intestinal pathologies triggered by undefined etiological factors ( 1 , 2 ). The pathogenesis of IBD is complex, and no consensus theory is yet available to fully elucidate the development of IBD.…”
Section: Introductionmentioning
confidence: 99%